MODEL DEVELOPMENT OF E-LEARNING EFFECTIVENESS IN FUNCTIONAL TRAINING OF PENERA AT METROLOGICAL RESOURCES DEVELOPMENT CENTER - Sukmana
The development of information and communication technology brings transformation to the field of education and training in the form of the application of e-learning. Penera Functional Training is carried out by utilizing e-learning methods for the purpose of increasing the quantity of Penera which is currently experiencing a deficit. In addition, the implementation of e-learning was accelerated by the Covid-19 pandemic, which limited physical and social activities. The acceleration of e-learning implementation causes symptoms of the ineffectiveness with a decrease in the level of competency test passing, complaints about the e-learning system, complaints about the delivery of material by instructor and complaints about the learning environment that has changed drastically which is considered to hinder learning achievement. The problem is suspected to stem from the non-optimal implementation of training with e-learning methods. The main problem is the absence of a model to measure the effectiveness of e-learning in training that can provide recommendations for improvement based on priorities with limited resources. Effectiveness needs to be measured on relevant measures to optimize the advantages of implementing e-learning, including satisfaction, training value, and competency test scores, as well as factors that are suspected to affect it, including information system, teacher, and environmental factors. Therefore, this study aims to develop a model of the effectiveness of e-learning and analyze the relationship of factors on the model in Penera Functional Training. This study used quantitative methods by testing 9 variables and 47 indicators. As many as 87 data were obtained through primary data collection, and secondary data were then processed using PLS-SEM techniques with the help of SmartPLS software. This research is expected to contribute to the literature and organization through knowledge of the relationship of factors in the developed model. This research fills a gap in the literature that, so far, there has been no research in the field of training using e-learning that examines complex effective measures in one empirical study, namely participant satisfaction, the final training score and competency test scores and knowing the factors that affect the effectiveness, namely system quality of LMS, information quality of LMS, services quality of LMS, instructor expertise, participant interaction and intention to use e-learning. The results obtained are 7 latent variables measured by 25 indicators that can explain the relationship between these latent variables. The service quality of LMS, instructor expertise and participant interaction significantly positively affect participant satisfaction. Participant satisfaction has a significant positive effect on the intention to use e-learning. Participant satisfaction and intention to use e-learning have a significant positive effect on the final training score. The final training score has a significant positive effect on the competency test score. Meanwhile, no significant positive influence was found between the five antecedent variables on intention to use e-learning, system quality of the LMS, and information quality of LMS on participant satisfaction. These results provide managerial implications that training effectiveness can be optimized by improving factors based on priority, namely services quality of LMS, instructor expertise and participant interaction, by paying attention to indicators that reflect each factor. The number of voluntary participants in advanced training can be increased by increasing participant satisfaction. The determination of the threshold for the value of passing training needs to be adjusted to optimize the percentage of passing the competency test. The new construct in this study is the expertise of teachers and participant interactions, which are proven to influence participant satisfaction by the hypothesis proposed positively.